Advanced Nanomedicines for Treating Refractory Inflammation-Related Diseases - Xiuxiu Wang; Xinran Song; Wei Feng; Meiqi Chang; Jishun Yang; Yu Chen (Nano-Micro Letters)
Highlights An overview of inflammation related diseases has been provided. The classification of nanomaterials commonly utilized in the treatment of various inflammatory diseases has been outlined. The current state of nanomedical applications with desirable therapeutic efficacy in the treatment of inflammatory diseases has been sum marized. The challenges and perspectives in the evolving field of nanomedicine for treating inflammatory diseases have been discussed and proposed in depth.